(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The field experiment was conducted during two successive rabi seasons of 2015-16 and 2016-17 in the research field of BARI, Gazipur, to evalute the effect of integrated nutrient management (INM) on seed yield and nutrient uptake of onion (var. BARI Piaz-1). The experiment was arranged in Randomized Complete Block Design (RCBD) with three replications having eight nutrient management packages following the INM principle. There were significant effects of INM on the seed yield, yield contributing characters and nutrient uptake of onion. The highest seed yield of 1278 and 1287 kg ha-1 was obtained from treatment poultry liter (PL) based trichocompost (TC) @ 3t ha-1 + chemical fertilizers (IPNS basis) and the minimum seed yield (395 kg ha-1 and 441 kg ha-1) in control (native fertility) treatment in 2015-2016 and 2016-2017, respectively. The N uptake by onion crop ranged from 37.1 to 141.5 kg ha-1 and 42.1 to 146.7 kg ha-1, P uptake from 2.9 to 13.5 kg ha-1 and 3.8 to 20.2 kg ha-1, K uptake from 24.5 to 76.7 kg ha-1 and 30.7 to 74.3 kg ha-1 and the S uptake ranged from 5.8 to 14.5 kg ha-1 and 6.1 to 18.8 kg ha-1 in two respective years. Hence, the PL based TC @ 3 t ha-1 + CF (IPNS) could be regarded as the best nutrient management package for achieving higher onion seed production in Grey Terrace Soil of Madhupur Tract (AEZ-28). Bangladesh J. Agril. Res. 46(4): 417-424, December 2021